Effect of Quarry Dust-Plantain Leaf Ash Filler on Asphalt Concrete Strength Performance (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The increasing demand for sustainable construction materials has driven the exploration of agricultural and industrial wastes as alternative fillers in asphalt concrete. This study investigates the synergistic effect of Plantain Leaf Ash (PLA), an agricultural waste, and Quarry Dust (QD), an industrial by-product, as composite fillers on the mechanical properties of asphalt concrete. The research aimed to determine the optimal blend that balances sustainability with structural performance. The sieve analysis, specific gravity, penetration, softening point and viscosity test were conducted to characterize the materials used. The coarse aggregate (gravel) was found to be gap-graded and deficient in intermediate particles. The bitumen penetration grade is 60/70 which has good temperature susceptibility and is workable, suited for paving applications. Experimental analyses were conducted using varying percentages of PLA (0%, 2%,4%, 6%, 8%, and 10%) and QD (0%, 2%,4%, 6%, 8%, and 10%) %) to assess their impact on the marshal stability, compressive strength and elastic modulus of asphalt mixture. The results revealed that the incorporation of Quarry Dust significantly enhanced both the Marshall stability, compressive strength and the elastic modulus, indicating its effectiveness as a mineral filler. Conversely, increasing PLA content consistently led to reductions in both compressive strength and elastic modulus, suggesting limited benefits in its role as a partial replacement. The optimal mix identified for superior mechanical performance is 10% QD with 0% PLA, achieving the highest strength and stiffness measures. These findings underscore the potential of Quarry Dust in asphalt concrete applications, while highlighting the need for further investigation into the long-term performance implications of using Plantain Leaf Ash in construction materials. The insights gained contribute to advancements in sustainable construction practices by optimizing material use in asphalt pavements.